Seroepidemiological Studies of Cutaneous Leishmaniasis in the Campeche State of México - Amalia Monroy-Ostria; Tayde Sosa-Cabrera; Beatriz Rivas -Sanchez; Rosaura Ruiz-Tuyu; Ana R Mendoza-Gonzalez; Luis Favila-Castillo (Memorias do Instituto Oswaldo Cruz, 1997)
Seroepidemiological studies of cutaneous leishmaniasis were carried out on 169 individuals in a rural area of the Campeche state of México. Fifty showed cutaneous lesions suggestive of leishmaniasis, 70% were parasite positive and 96% skin test positive. An overall 40% positivity to skin test with Montenegro's antigen was found. Most of the affected individuals were males from 11 to 30 years-old. Antibodies were determined by immunofluorescent antibody test (IFA) and by Western blot. Two antigen preparations were used, one from a Leishmania mexicana strain which produced localized cutaneous leishmaniasis (LCL) and the other from a diffuse cutaneous leishmaniasis (DCL). In the general population from the area of study 19% gave positive IFA tests with DCL antigen and 20% with LCL antigen while for the patients 67% gave positive IFA tests with DCL and 71% with LCL. By Western blot analysis most of the patients recognized more antigens in the DCL than in the LCL strain. In the DCL strain 78% of patients recognized a 105 kDa, 34% a 139 kDa, 28% a 117 kDa and 26% a 205 kDa MW antigen. In the LCL strain 40% of patients recognized a 205 kDa and 22% a 175 kDa antigens